Distribution of Vitamin E, squalene, epicatechin, and rutin in common buckwheat plants (Fagopyrum esculentum Moench) - Kalinová, Jana; Tříska, Jan; Vrchotová, Naděžda (Journal of agricultural and food chemistry, 2006)
Buckwheat leaves and young parts of the plant are consumed in some countries as a vegetable. Green flour, obtained by milling of the dried plants, is used as a natural food colorant. The distribution of vitamin E, squalene, epicatechin, and rutin (as the most important antioxidants) within buckwheat plants, as well as changes of their content within leaves during the growing season, were determined by GC-MS and HPLC analyses. alpha-Tocopherol was found as the main component of vitamin E in all parts of the plant; epicatechin and squalene were also detected. For the use of buckwheat as an antioxidant source in the human diet, the most suitable part of the plants seems to be the leaves and the flowers at the stage of full flowering due to the considerable amounts of rutin and epicatechin. alpha-Tocopherol content correlates positively with temperature, drought, and duration of solar radiation. Certain differences appear among varieties of buckwheat, especially in their squalene and rutin contents.
Keywords: financování organizované; Squalene; Gas Chromatography-Mass Spectrometry; vysokoúčinná kapalinová chromatografie; alfa-tokoferol; Financing, Organized; Catechin; Rutin; Chromatography, High Pressure Liquid; alpha-Tocopherol; Fagopyrum; Plant Leaves; plynová chromatografie s hmotnostně spektrometrickou detekcí; skvalen; listy rostlin; rutin; katechin